Interaction studies unveil potential binding sites on bovine serum albumin for gut metabolite trimethylamine n-oxide (TMAO) - Awadhesh Kumar Verma; Payal Gulati; GBVS Lakshmi; Anand Mohan; Neeta Raj Sharma; Pratima R. Solanki; Anil Kumar (BMC Chemistry)
Abstract Trimethylamine-N-oxide (TMAO) is gut microbiota-derived metabolite, plays a critical role in human health and diseases such as metabolic, cardiovascular, colorectal cancer and, neurological disorders. Binding interactions between TMAO and serum albumins are crucial to understand the impact of TMAO on disease mechanisms. However, detailed insights into the interaction mechanisms, preferred binding locations, and conformational changes in BSA upon binding TMAO are still unclear. TMAO interacts with serum albumin in human body and thus, a model study of interaction for TMAO-BSA conjugate is presented in support of it. Decrease in absorbance intensity of protein upon interaction with metabolites reveals conjugate formation, while fluorescence spectroscopy indicate static quenching. Contact angle measurements further reveal the hydrophilic nature of the TMAO-BSA complex, while CD and FTIR support conformational changes in BSA upon binding but structure remain intact. Computational studies, such as molecular docking, molecular dynamics simulation and, MM/GBSA, confirm a stable complex with a binding energy of − 3.6 kcal/mol. These findings provide a foundation for understanding the pharmacodynamics and pharmacokinetics of TMAO and may aid in developing strategies for treating diseases, such as chronic kidney disease and neurological disorder where TMAO-serum albumins interaction are implicated.